Structural modification of empty and partially filled paddy grain through hydrothermal pre-treatment as a novel substrate for fermentable glucose production - Abu Bakar, Nurul Ain; Roslan, Ahmad Muhaimin; Hassan, Mohd Ali; Abdul Rahman, Muhammad Daaniyall; Mohamad, Rozyanti; Ibrahim, Khairul Nadiah (John Wiley & Sons, 2022)
In this study, two conditions of empty and partially filled paddy grain (EPFG) (unground and ground) are pre-treated using a mild hydrothermal process at 120 °C at 30–120 min. The pre-treatment condition which shows potential structural changes for sugar conversion (gelatinization of starch, reduction of hemicellulose to 11.8%, and increased in cellulose to 43.3%) involves combination of dry grinding and hydrothermal pre-treatment at 60 min. In this condition, the starch and sugars released in the liquid fraction is high at 127 and 37.1 mg g−1, respectively, which can easily be converted into glucose without the need of enzyme usage. The effectiveness of the pre-treatment on EPFG structural changes is further confirmed through scanning electron microscopy (SEM) and X-ray diffraction (XRD), showing disruption of structures leading to amorphous biomass. Glucose production of pre-treated ground EPFG (G-EPFG) shows higher value at 30.13 g L−1 for 10% solid loading than the untreated samples. Overall, the results suggest that EPFG produced as waste in paddy milling factories can be a potential feedstock for a biorefinery based on the findings and processes derived from this study.